Biopsychosocial correlates of life satisfaction among adolescents in Selangor, Malaysia - Chiong, Hoe Nee (2015)
Adolescents who are physically and psychologically healthy are invaluable assets to the nation. However, increasing cases of behavioral problems among adolescents in Malaysia may reflect their dissatisfaction in life. When they are dissatisfied with their life, they get involved in maladjustment behaviors. Thus, it is crucial and necessary to understand adolescents' life satisfaction and its contributing factors. Life satisfaction is influenced by multiple factors such as biological. psychological and social factors. Analyzing "bio", "psycho" and "social" factors concurrently are important in understanding life satisfaction. These three components are regarded as "biopsychosocial" factors. The main objective of this study is to examine biopsychosocial (physical health, body mass index, resilience, locus of control, family economic hardship, connectedness to famiIy, connectedness to friends and connectedness to school) correlates of life satisfaction among adolescents in Selangor. This study used a quantitative approach and non-experimental correlational research design. The respondents of the current study consisted of 451 secondary school students aged between 14 and 17 years old. They were identified through multi-stage cluster sampling technique from secondary schools in Selangor. The data were collected using self-administered questionnaires in a class setting. Six well-established instruments were used to assess variables of the study. Descriptive, bivariate and multivariate statistics were utilized in data analysis. Pearson correlation analysis showed that age of the respondents, physical heath, resilience, locus of control, family economic hardship, connectedness to family and connectedness to school were significantly correlated to life satisfaction. In addition, physical health, locus of control, family economic hardship, connectedness to family and connectedness to school were significantly related to resilience. The result of the t test showed that there was no significant difference in life satisfaction between male and female adolescents. Meanwhile, ANOYA showed no differences in life satisfaction between body mass index groups among adolescents. Multiple regression analysis found that background variables (age, father's education, mother's education and family income) and biopsychosocial variables (physical health, resilience, locus of control, family economic hardship, connectedness to family and connectedness to school) explained 27.2% of variance in adolescents' life satisfaction. Connectedness to family appeared as the strongest predictor of life satisfaction among adolescents, followed by physical health. Mediation analysis also showed that resilience partially mediated the relationship between physical health, locus of control, connectedness to family and connectedness to school with life satisfaction among adolescents. The present study highlighted the importance of biopsychosocial factors in promoting life satisfaction among secondary students in Selangor. The contribution of these variables on life satisfaction were indirect though resilience. Relationships between the independent variables and life satisfaction as dependent variable, with resilience as partial mediator implied that life satisfaction among adolescents can be enhanced if they possess personal resources or skills such as resilience in overcoming adversity in life. This study provides implications for theory and knowledge advancement in the field of human development specifically on life satisfaction among adolescents. It also provides practical implications to practitioners in conducting programs and activities aimed to improve adolescents' life satisfaction.